A Fast Rigid Registration Algorithm for Medical Images (Journal of Fiber Bioengineering and Informatics, 2014)
Image registration is a vital research branch in medical image processing and analysis. In this paper, weproposed a new framework for rigid medical image registration. It can also be regarded as a pre-processingof non-rigid image registration algorithms. The interest of the algorithm lies in its simplicity and higheffciency. In the registration algorithm, we firstly segmented the reference image and float image intotwo parts: tissue parts and background parts. Then the centers of the two images were located throughperforming distance transform on the two segmented tissue images. Finally, we detected the longestradius of the two tissue regions, by which we determined the rotating angle. We tested the registrationalgorithm on dozens of medical images, and the experimental results show us that the algorithm iscompetent for medical image registration.
Keywords: Image Registration; Medical Image; Image Segment; Distance Transformation